Conversion of sulfur compounds and microbial community in anaerobic treatment of fish and pork waste. (June 2018) - He, Ruo; Yao, Xing-Zhi; Chen, Min; Ma, Ruo-Chan; Li, Hua-Jun; Wang, Chen; Ding, Shen-Hua
Highlights: The conversion of TS, SO4 2− -S, S 2−, methionine, cysteine followed the first-order kinetics. CH3 SH was the major sulfur component during the degradation of fish and pork waste. Most sulfur compounds in the fish and pork waste was converted into VSCs. C/N value greatly influenced on the microbial community in the fish and pork waste. Abstract: Volatile sulfur compounds (VSCs) are not only the main source of malodor in anaerobic treatment of organic waste, but also pose a threat to human health. In this study, VSCs production and microbial community was investigated during the anaerobic degradation of fish and pork waste. The results showed that after the operation of 245 days, 94.5% and 76.2% of sulfur compounds in the fish and pork waste was converted into VSCs. Among the detected VSCs including H2 S, carbon disulfide, methanethiol, ethanethiol, dimethyl sulfide, dimethyl disulfide and dimethyl trisulfide, methanethiol was the major component with the maximum concentration of 4.54% and 3.28% in the fish and pork waste, respectively. The conversion of sulfur compounds including total sulfur, SO4 2− -S, S 2−, methionine and cysteine followed the first-order kinetics. Miseq sequencing analysis showed that Acinetobacter, Clostridium, Proteus, Thiobacillus, Hyphomicrobium and Pseudomonas were the main known sulfur-metabolizing microorganisms in the fish and pork waste. The C/N value had most significant influence on the microbial community in the fish and pork waste. A main conversion of sulfur compounds with CH3 SH as the key intermediate was firstly hypothesized during the anaerobic degradation of fish and pork waste. These findings are helpful to understand the conversion of sulfur compounds and to develop techniques to control ordor pollution in the anaerobic treatment of organic waste.